Propuesta de un modelo de gestión orientado al desarrollo del turismo rural comunitario en Cuniburo, parroquia Cangahua, cantón Cayambe, provincia de Pichincha - Lanchimba Ulcuango, Blanca Pastora (2021)
The present investigation called "PROPOSAL OF A MANAGEMENT MODEL CONCERNED WITH THE DEVELOPMENT OF RURAL COMMUNITY TOURISM IN CUNIBURO, CANGAHUA PARISHION, CAYAMBE CANTON, PICHINCHA PROVINCE" has a qualitative approach at an exploratory level, therefore, three objectives were established; For the fulfillment of the first objective, a situational diagnosis of Cuniburo in the physical, ecological, administrative, sociocultural and economic-productive areas was carried out, which were collected in bibliographic sources such as scientific articles, magazines, undergraduate theses, parish and cantonal PDyOT documents, Cayambe tourist guide and the cantonal tourism development plan, as well as information was obtained during field trips to the community; the non-probabilistic method was applied by convenience and the survey technique for the analysis of the tourism demand. To achieve the second objective, which consisted of analyzing the current tourism management, key internal and external informants were identified through intentional sampling and a structured interview was applied, which allowed determining that the management of community tourism in Cuniburo is deficient because the planning of tourism activities is done empirically, mainly due to lack of knowledge of the activity and lack of advice; Based on the analysis of the community situation and the current tourism reality, a mapping of actors and a cross SWOT analysis were carried out, which resulted in the strategies to be taken into account for the development of the proposal. For the scope of the third objective, the methodology proposed by García (2017) was applied, which proposes to develop a management model based on basic indicators that characterize the tourism management of a territory in order to promote tourism development in the communities. In this way, strategies were proposed for the development of the management model, structured by the creation of a committee for tourism management, the creation of alliances and agreements, education and training, tourist offer, promotion and digital dissemination of the same, and finally monitoring and control. The purpose of the research is to provide the community with an instrument that allows the creation of coordination between the entities involved and the community in order to improve local tourism management.